Faculty Perception of “Presence” in the Online Environment - Anita Samuel (Adult Education Research Conference, 2015)
Like students, faculty also experience isolation in the online learning environment. This session presents the findings of a pilot study into faculty sense of alienation and the strategies that faculty have employed to “be there” and “be together” with their students in the online environment.
Keywords: online education; online faculty; sense of presence; alienation